1981
DOI: 10.1073/pnas.78.7.4584
|View full text |Cite
|
Sign up to set email alerts
|

Platelet factor 4 is chemotactic for neutrophils and monocytes.

Abstract: Platelet factor 4 is shown to be a chemotactic protein for human polymorphonuclear leukocytes and monocytes at concentrations found in human serum and reached locally in injured tissue. The maximum chemotactic response to platelet factor 4 nearly equals that achieved with saturating concentrations ofthe chemotactic activity derived from the fifth component of human complement, C5. Cells desensitized to C5 chemotactic activity retain chemotactic responsiveness to platelet factor 4. Serum contains inhibitory cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
154
2
3

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(163 citation statements)
references
References 30 publications
(19 reference statements)
4
154
2
3
Order By: Relevance
“…Early reports claimed the ability of PF-4 to induce neutrophil and monocyte chemotaxis (27,28). However, in a more recent report we have shown that, at least for neutrophils, highly purified PF-4 lacks such activity and that the previously observed effects were most likely due to contamination by other chemokines (16).…”
Section: Pf-4 Lacks Chemotactic Activity On Human Monocytes But Inducmentioning
confidence: 77%
“…Early reports claimed the ability of PF-4 to induce neutrophil and monocyte chemotaxis (27,28). However, in a more recent report we have shown that, at least for neutrophils, highly purified PF-4 lacks such activity and that the previously observed effects were most likely due to contamination by other chemokines (16).…”
Section: Pf-4 Lacks Chemotactic Activity On Human Monocytes But Inducmentioning
confidence: 77%
“…Although platelets are anuclear cell fragments, they possess a cellular machinery comparable to leukocytes in many aspects. Platelets have a cytoskeletal framework that allows cell motion, they can generate superoxide radicals (32), can release chemotactic factors for neutrophils, monocytes, and eosinophils (33)(34)(35), and have all the known adhesive components required for cell extravasation: a putative ligand for P-selectin, a j32 integrin (LFA-1) (36), PECAM-1 (37), and several f31 integrins (38).…”
Section: Discussionmentioning
confidence: 99%
“…Plasminogen activators are serine proteinases con-verting plasminogen into plasmin, which plays an important role in the dissolution of fibrin clots (Saksela 1985) and can degrade cartilage proteoglycan (Mochan and Keler 1984). According to some authors, coagulation products, such as platelet factor-4 (Deuel et al 1981). thrombin (Bar-Shavit et al 1983).…”
Section: Discussionmentioning
confidence: 99%